2021
DOI: 10.3389/fbioe.2021.811287
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Fractionation of the Tobacco Stalk Lignin for Customized Value-Added Utilization

Abstract: The value-added utilization of tobacco stalk lignin is the key to the development of tobacco stalk resources. However, the serious heterogeneity is the bottleneck for making full use of tobacco stalk lignin. Based on this, lignin was separated from tobacco stalk through hydrothermal assisted dilute alkali pretreatment. Subsequently, the tobacco stalk alkaline lignin was fractionated into five uniform lignin components by sequential solvent fractionation. Advanced spectral technologies (FT-IR, NMR, and GPC) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Figure 4C shows that TG/DTG curves of the lignins are presented. Notably, the thermal degradation behavior of different lignin samples was diversiform, which was influenced by their inherent structures, that is, the chemical linkages, the abundance of functional groups, and the degree of condensation ( Liu et al, 2021 ; Wang et al, 2022 ). It has been reported that the thermal decomposition behavior of lignin polymer was correlated to its molecular weight, whereas an inconspicuous tendency was found in this study, and this could be explained by their little differences in molecular weights ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4C shows that TG/DTG curves of the lignins are presented. Notably, the thermal degradation behavior of different lignin samples was diversiform, which was influenced by their inherent structures, that is, the chemical linkages, the abundance of functional groups, and the degree of condensation ( Liu et al, 2021 ; Wang et al, 2022 ). It has been reported that the thermal decomposition behavior of lignin polymer was correlated to its molecular weight, whereas an inconspicuous tendency was found in this study, and this could be explained by their little differences in molecular weights ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme 2 , industrial alkali lignin (KL) from corn cob was fractionated sequentially using five recoverable organic solvents. The specific procedure in detail has been explained in our previous studies [ 23 ]. Finally, the lignin fractions collected from n-butanol, ethanol, methanol, and dioxane were referred as F1, F2, F3, and F4, respectively, and F5 was an insoluble residue.…”
Section: Methodsmentioning
confidence: 99%
“…In order to solve the problems of poor reactivity and solubility of lignin, dioxane, dimethyl sulfoxide and high-concentration alkali liquor are usually used as reaction solvents in the production of lignin-based flocculants [ 21 , 22 ]. These reaction solvents can cause serious environmental burden and high cost [ 23 ]. Ethanol as a reaction solvent has excellent application prospects due to its low price, non-toxicity, and easy recovery [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of tobacco stalk can make full use of resources, provided ecological benefits, create economic benefits, and promote sustainable development. [10][11][12] In fact, tobacco stalk fiber (TSF) is often used as an industrial raw material because it contains cellulose, hemicellulose, lignin, and other organic substances. It is possible to extract lignin, xylan, and other chemical raw materials from tobacco stalk and prepare nano-cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…However, the comprehensive utilization of tobacco stalks is insufficient, and they are often directly treated as garbage or fuel, giving rise to a great waste of biological resources and serious environmental pollution. The utilization of tobacco stalk can make full use of resources, provided ecological benefits, create economic benefits, and promote sustainable development 10–12 . In fact, tobacco stalk fiber (TSF) is often used as an industrial raw material because it contains cellulose, hemicellulose, lignin, and other organic substances.…”
Section: Introductionmentioning
confidence: 99%